2014
DOI: 10.1186/1750-9378-9-12
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein Barr-encoded BART-6-3p microRNA affects regulation of cell growth and immuno response in Burkitt lymphoma

Abstract: BackgroundBurkitt lymphoma is an aggressive B-cell lymphoma presenting in three clinical forms: endemic, sporadic and immunodeficiency-associated. More than 90% of endemic Burkitt lymphoma carry latent Epstein-Barr virus, whereas only 20% of sporadic Burkitt lymphoma are associated with Epstein-Barr infection. Although the Epstein-Barr virus is highly related with the endemic form, how and whether the virus participates in its pathogenesis remains to be fully elucidated. In particular, the virus may impair cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 45 publications
1
63
0
Order By: Relevance
“…Our data shows that the mRNA transcription of PTEN itself is not significantly differentially expressed between EBV positive and negative BLs. However, Ambrosio et al found that protein levels of PTEN are significantly lower in EBV positive BLs compared to negatives (53). This suggests a mechanism in which viral miRNAs interact with PTEN causing a translational inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Our data shows that the mRNA transcription of PTEN itself is not significantly differentially expressed between EBV positive and negative BLs. However, Ambrosio et al found that protein levels of PTEN are significantly lower in EBV positive BLs compared to negatives (53). This suggests a mechanism in which viral miRNAs interact with PTEN causing a translational inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we chose BART6-3p as our study object, which is highly expressed in latency II malignancy and plays a role in tumorigenesis [43][44][45][46] , but has no clear functions related to immune regulation. By using a cDNA microarray technique, we found that 49 genes were downregulated upon BART6-3p mimic transfection in PBMCs, which are natural host cells of EBV infection, and most of them participated in the type I IFN virus response, as well as the RIG-I-like receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, EBV miRNAs regulate the IFNγ-STAT1 pathway in EBV + NK cells by downregulating IFNγ transcriptional regulator T-bet (BART20-5p), IFNγ (BART20-5p), and STAT1 (BART8) (Huang and Lin 2014;Lin et al 2013). Inhibition of BART6-3p in a BL cell line caused upregulation of the IL-6 receptor chains (p80 and gp130) at the mRNA and protein level, indicating that BART6-3p may affect IL-6 signaling (Ambrosio et al 2014).…”
Section: Ebv Mirnasmentioning
confidence: 99%
“…These miRNAs are organized in Lerner et al (1981), Clarke et al (1991), Komano et al (1999), Nanbo et al (2002Nanbo et al ( , 2005, Ruf et al (2005) miR-BHRF1-3 Downregulates T cell attracting chemokine CXCL-11 Xia et al (2008) miR-BART2-5p Inhibition of this miRNA results in increased NK-cell killing in vitro Nachmani et al (2009) miR-BART15 Downregulates NLRP3 Haneklaus et al (2012) miR-BART20-5p Downregulates IFNγ transcriptional regulator T-bet and IFNγ Huang and Lin (2014), Lin et al (2013) miR-BART8 Inhibits STAT1 expression Huang and Lin (2014) miR-BART6-3p Downregulation of IL-6 receptor chains Ambrosio et al (2014) clusters and are expressed during all latency stages (and thus in EBV-associated tumors), although their expression levels differ between these stages (Amoroso et al 2011;Motsch et al 2012;Qiu et al 2011). miRNAs have been detected in EBV virions, allowing their release in newly infected cells (Jochum et al 2012a).…”
Section: Ebv Mirnasmentioning
confidence: 99%